The effect of body mass index on clinical response to abatacept as a first-line biologic for rheumatoid arthritis: 6-month results from the 2-year, observational, prospective ACTION study - Mariette, Xavier; Lorenz, Hanns-Martin (Joint bone spine, 2017)
Objective:To assess the impact of baseline body mass index (BMI) on the efficacy and retention of intravenous abatacept at 6 months in biologic-naïve patients with rheumatoid arthritis (RA). Methods: This was a 6-month analysis of a 2-year, non-interventional, international, prospective study. Baseline characteristics, clinical response and retention rates were compared by BMI subgroup: underweight/normal, overweight and obese (<25, 25 to <30 and ≥30kg/m2, respectively). Results: BMI was reported in 643/672 (96%) patients: 264 (41%) were underweight/normal, 224 (35%) overweight and 155 (24%) obese. At baseline, the obese group had more active disease (mean [95% confidence intervals] 28-joint Disease Activity Score [C-reactive protein; derived] 4.6 [4.5, 4.7], 4.8 [4.7, 5.0] and 5.1 [4.9, 5.2] for underweight/normal, overweight and obese groups, respectively), a higher prevalence of metabolic disorders, a greater proportion of women and a lower proportion of patients with rheumatoid factor positivity. There were no significant differences in the percentages of patients achieving a good/moderate European League Against Rheumatism response by BMI group (80.7, 86.1 and 77.0% for underweight/normal, overweight and obese groups, respectively; P=0.178). Overall retention rates at 6 months did not differ across groups (89, 92 and 89% for underweight/normal, overweight and obese groups, respectively; log-rank P=0.382). After adjustment for baseline characteristics, BMI was not significantly associated with risk of discontinuation (reference BMI<25kg/m2; hazard ratio [95% confidence intervals] 0.46 [0.22, 0.99] and 0.69 [0.34, 1.41] for overweight and obese patients, respectively). Conclusion: BMI does not impact abatacept clinical response or retention in biologic-naïve patients with RA.
Available online 30 December 2016
Gesehen am 02.10.2018